Split the summand into partial fractions,
![\frac1{n(2n+1)} = \frac1n - \frac2{2n+1}](https://img.qammunity.org/2023/formulas/mathematics/college/ta5mzz7u7a3p2uamazl736y3333njt4gyx.png)
At even integers, the Riemann zeta function has the equivalent form
![\zeta(2n) = ((-1)^(n+1) B_(2n) 2^(2n-1) \pi^(2n))/((2n)!)](https://img.qammunity.org/2023/formulas/mathematics/college/7uhahnacviv2bjmba1iawh791se650be0l.png)
where
denotes the n-th Bernoulli number.
Now the sum we want is
![\displaystyle \sum_(n=1)^\infty (\zeta(2n))/(n(2n+1)4^(2n)) = -\frac12 \sum_(n=1)^\infty ((-1)^n B_(2n))/(n (2n)!) \left(\frac{\pi^2}4\right)^n + \sum_(n=1)^\infty ((-1)^n B_(2n))/((2n+1) (2n)!) \left(\frac{\pi^2}4\right)^n](https://img.qammunity.org/2023/formulas/mathematics/college/4vsasciuama59iv44umtc0tko5yy7nudv4.png)
Recall the series expansion for cot(x), valid for 0 < x < π :
![\cot(x) = \displaystyle \sum_(n=0)^\infty ((-1)^n B_(2n) 2^(2n) x^(2n-1))/((2n)!)](https://img.qammunity.org/2023/formulas/mathematics/college/vgwy8k9ej5v1tho1xtce0sjtyfkiqhhhxk.png)
from which we have
![x \cot(x) = \displaystyle \sum_(n=0)^\infty ((-1)^n B_(2n))/((2n)!) \left(4x^2\right)^n](https://img.qammunity.org/2023/formulas/mathematics/college/lb9glvvgnxm6f0u2w9yq9gnf31mh6v9vby.png)
and letting
, we get
![-\frac{\sqrt x}2 \cot\left(\frac{\sqrt x}2\right) = \displaystyle \sum_(n=0)^\infty ((-1)^(n+1) B_(2n))/((2n)!) x^n](https://img.qammunity.org/2023/formulas/mathematics/college/d6frhyyibyxfebiekwiih5kndeeypx3sw8.png)
Let
![f(x) = \displaystyle \sum_(n=1)^\infty ((-1)^n B_(2n))/(n (2n)!) x^n](https://img.qammunity.org/2023/formulas/mathematics/college/rv3imlvb7s41evovjk3w0p8vm9rwrv3gcn.png)
Differentiating both sides gives
![f'(x) = \displaystyle \sum_(n=1)^\infty ((-1)^n B_(2n))/((2n)!) x^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/vfckgg9rt0jklay64o9iqxsqlh3snpaxsy.png)
so that
![x f'(x) = \frac{\sqrt x}2 \cot\left(\frac{\sqrt x}2\right) - 1](https://img.qammunity.org/2023/formulas/mathematics/college/rdqr320lqascd42hb747zt7qrca76zbjjw.png)
By the fundamental theorem of calculus,
![f'(x) = \frac1{2\sqrt x} \cot\left(\frac{\sqrt x}2\right) - \frac1x](https://img.qammunity.org/2023/formulas/mathematics/college/sge5b60glrljynezr23mph51lilclt875r.png)
![\implies f(x) = f(0) + 2 \ln\left(\sin\left(\frac{\sqrt x}2\right)\right) - \ln(x)](https://img.qammunity.org/2023/formulas/mathematics/college/obyuy2aptyloc7q1o6j71s1uowgngbkw9r.png)
We observe that as x approaches 0, the series vanishes, so we must have
![\displaystyle f(0) = \lim_(x\to0^+) 2\ln\left(\sin\left(\frac{\sqrt x}2\right)\right) - \ln(x) = -2\ln(2)](https://img.qammunity.org/2023/formulas/mathematics/college/d07k1qd6a0489h8752sauqnva5xhcy2htp.png)
Similarly, let
![g(x) = \displaystyle \sum_(n=1)^\infty ((-1)^n B_(2n))/((2n+1) (2n)!) x^(2n+1)](https://img.qammunity.org/2023/formulas/mathematics/college/q9sxw83aih1trf3yaoc02t8fbx62v0p62o.png)
with g(0) = 0, and differentiate to get
![g'(x) = \displaystyle \sum_(n=1)^\infty ((-1)^n B_(2n))/((2n)!) (x^2)^n](https://img.qammunity.org/2023/formulas/mathematics/college/kscnkxlk5bbb4jvonvmkw4bzz7cqmcx97a.png)
We then have
![g'(x) = \frac x2 \cot\left(\frac x2\right) - 1](https://img.qammunity.org/2023/formulas/mathematics/college/v74g9539i653gnqiicrrm3acpd0mtr0uzz.png)
and by the fundamental theorem of calculus,
![g(x) = \displaystyle \int_0^x \frac t2 \cot\left(\frac t2\right) \, dt - x](https://img.qammunity.org/2023/formulas/mathematics/college/jdfrpsu36kfhjk1orbznui3gi6nohabgjg.png)
or
![(g(\sqrt x))/(\sqrt x) = \displaystyle \frac1{\sqrt x} \int_0^(\sqrt x) \frac t2 \cot\left(\frac t2\right) \, dt - 1](https://img.qammunity.org/2023/formulas/mathematics/college/4ca7i2cqqotwpejs4bwja6aqt2bzvd9kdo.png)
The sum we want is then
![\displaystyle \sum_(n=1)^\infty (\zeta(2n))/(n(2n+1)4^(2n)) = -\frac12 f\left(\frac{\pi^2}4\right) + \frac1{\sqrt{\frac{\pi^2}4}} g\left(\sqrt{\frac{\pi^2}4}\right) = -\frac12 f\left(\frac{\pi^2}4\right) + \frac2\pi g\left(\frac\pi2\right)](https://img.qammunity.org/2023/formulas/mathematics/college/ghgu2zs0bthpeiqp1aydruaf5oxtiw5pas.png)
Now we turn our attention to
![\displaystyle \int_0^(\frac\pi2) \frac x2 \cot\left(\frac x2\right) \, dx = 2 \int_0^(\frac\pi4) x \cot(x) \, dx](https://img.qammunity.org/2023/formulas/mathematics/college/h3nfkxj1f39wnj7khw8ri28lx0upgf7648.png)
Integrating by parts gives
![\displaystyle \int_0^(\frac\pi4) x \cot(x) \, dx = -\frac\pi8 \ln(2) - \int_0^(\frac\pi4) \ln(\sin(x)) \, dx](https://img.qammunity.org/2023/formulas/mathematics/college/rxit1qzdmpols51d1cgmogpedleyzijh7x.png)
Using the identity from your earlier question [26989784],
![\displaystyle -\int_0^(\frac\pi4) \ln(\sin(x)) \, dx = \frac\pi8 \ln(2) + \frac12 \sum_(k=1)^\infty \frac1{k^2} \sin\left(\frac{k\pi}2\right) \\\\ = \frac\pi8 \ln(2) + \frac12 \sum_(k=0)^\infty ((-1)^k)/((2k+1)^2) \\\\ = \frac\pi8 \ln(2) + \frac G2](https://img.qammunity.org/2023/formulas/mathematics/college/mt2nssrrkslog7q0mimcacv0zgvtw2oqe9.png)
where G is Catalan's constant.
So, it would seem
![\displaystyle \sum_(n=1)^\infty (\zeta(2n))/(n(2n+1)4^(2n)) = \boxed{\ln(\pi) - \ln(2) + \frac{2G}\pi - 1}](https://img.qammunity.org/2023/formulas/mathematics/college/wurri662rvgl3t2lzvzhrnb6hyyrc8u2rv.png)